GluA1 AMPAR subunit deletion reduces the hedonic response to sucrose but leaves satiety and conditioned responses intact - Austen, Joseph M.; Sprengel, Rolf; Sanderson, David (Scientific reports, 2017)
The GluA1 subunit of the AMPA receptor has been implicated in schizophrenia. While GluA1 is important for cognition, it is not clear what the role of GluA1 is in hedonic responses that are relevant to the negative symptoms of disorders such as schizophrenia. Here, we tested mice that lack GluA1 (Gria1 -/- mice) on consumption of sucrose solutions using a licking microstructure analysis. GluA1 deletion drastically reduced palatability (as measured by the mean lick cluster size) across a range of sucrose concentrations. Although initial lick rates were reduced, measures of consumption across long periods of access to sucrose solutions were not affected by GluA1 deletion and Gria1 -/- mice showed normal satiety responses to high sucrose concentrations. GluA1 deletion also failed to impair flavour conditioning, in which increased intake of a flavour occurred as a consequence of prior pairing with a high sucrose concentration. These results demonstrate that GluA1 plays a role in responding on the basis of palatability rather than other properties, such as the automatic and learnt post-ingestive, nutritional consequences of sucrose. Therefore, Gria1 -/- mice provide a potential model of anhedonia, adding converging evidence to the role of glutamatergic dysfunction in various symptoms of schizophrenia and related disorders.